1975
DOI: 10.1139/b75-083
|View full text |Cite
|
Sign up to set email alerts
|

Pyrimidine metabolism in seeds and seedlings of jack pine (Pinus banksiana)

Abstract: PITEL, J., and D. J. DURZAN. 1975. Pyrimidine metabolism in seeds and seedlings ofjack pine (Pinus banksiana). Can. J. Bot. 53: 673486. Jack pine seedlings rapidly converted radioactive thymine-6-IH to dihydrothymine, p-ureidoisobutyric acid, and P-aminoisobutyric acid. Autoradiographsof hypocotyl cells showed radioactivity largely in the cytoplasm. A small percentage of radioactivity from thymine-2-I4C was salvaged via uracil for the synthesis of RNA. DNA was not labelled significantly. The occurrence of a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
4
1

Year Published

1979
1979
2001
2001

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
4
4
1
Order By: Relevance
“…6) indicates that the ability to synthesize pyrimidine nucleotides de novo was low in dry embryos and gradually increased as germination progressed. Similarly to our observation, an extensive amount of the radioactivity from labeled orotate was recovered into nucleic acids of jack pine seedlings (Pitel and Durzan, 1975). The relatively poor utilization of orotate at the end of the desiccation period (10 d PDT) may be ascribed to the low specific activity of orotate phosphoribosyl transferase (OPRT) ( Table 1) which, in concert with orotidine monophosphate decarboxylase (Ashihara, 1978;Santoso and Thornburg, 1998) catalyzes the conversion of orotate to UMP (steps 2 and 9, Fig.…”
Section: Discussionsupporting
confidence: 81%
“…6) indicates that the ability to synthesize pyrimidine nucleotides de novo was low in dry embryos and gradually increased as germination progressed. Similarly to our observation, an extensive amount of the radioactivity from labeled orotate was recovered into nucleic acids of jack pine seedlings (Pitel and Durzan, 1975). The relatively poor utilization of orotate at the end of the desiccation period (10 d PDT) may be ascribed to the low specific activity of orotate phosphoribosyl transferase (OPRT) ( Table 1) which, in concert with orotidine monophosphate decarboxylase (Ashihara, 1978;Santoso and Thornburg, 1998) catalyzes the conversion of orotate to UMP (steps 2 and 9, Fig.…”
Section: Discussionsupporting
confidence: 81%
“…Although the exact degradation pathway of orotate could not be estimated from the data obtained here, orotate may be converted to uridine nucleotides and then catabolized via uracil by the reductive pathway. This speculation does not contradict the report of Pitel and Durzan (1975), who demonstrated that a small amount of radioactivity from [4-14 C]orotic acid was incorporated into i-alanine in jack pine seedlings. Further degradation of i-alanine may be rapid in white spruce cells, because radioactivity from [6-14 C]orotic acid was recovered as 14 CO 2 .…”
Section: Discussionsupporting
confidence: 69%
“…Compared with uridine and uracil, orotic acid was a good precursor for the pyrimidine nucleotides, especially for nucleic acids in white spruce. Pitel and Durzan (1975) also reported that most of the radioactivity from [4-14 C]orotate was incorporated into nucleic acids in jack pine seedlings. These results obtained from conifers are different from the data obtained from suspension-cultured C. roseus cells (Kanamori-Fukuda et al 1981) and carrot cells , where uridine is the most efficient precursor for the nucleotides and nucleic acid synthesis.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Compared to other plants, a very active adenine salvage pathway for nucleotide biosynthesis was noted. For pyrimidines, Durzan and his co‐workers (Durzan et al 1973; Pitel and Durzan 1975) examined the metabolism of exogenously supplied radioactive uracil, thymine, thymidine, and orotate in Pinus banksiana seeds and seedlings. Biosynthesis of nucleic acids via the de novo and salvage pathways of pyrimidine nucleotides and degradation of pyrimidine bases were demonstrated by their tracer experiments.…”
Section: Introductionmentioning
confidence: 99%